Smaller AgBr Nanoparticle Embedded in One-Dimensional Poly(vinyl pyrrolidone) Fibers - Bai, Jie; Zhang, Yongfeng; Li, Chunping; Zhang, Jianbin (Asian Journal of Chemistry, 2011)
A new series of AgBr/poly(vinyl pyrrolidone) (PVP) composite fibers have been prepared successfully by electrospinning technology and Sol-Gel method. This is a novel and simple approach. At first, we use Sol-Gel process to prepare thinner AgBr nanoparticles in the poly(vinyl pyrrolidone) solution and then the solution are electrospun to obtain AgBr/poly(vinyl pyrrolidone) composite nanofibers. The final products obtained were thoroughly characterized by transmission electron microscopy, scanning electron microscopy, X-ray diffraction patterns and X-ray photoemission spectroscopy.